2015
DOI: 10.1186/s12886-015-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

One year results of intravitreal ranibizumab monotherapy for retinal angiomatous proliferation: a comparative analysis based on disease stages

Abstract: BackgroundRetinal angiomatous proliferation (RAP) has been known as a variant of exudative age-related macular degeneration (AMD) with a unfavorable prognosis. To evaluate the effect of ranibizumab administered initially as three loading doses for patients with various stages of RAP.MethodsA retrospective chart review of 40 patients (41 eyes) with RAP was conducted. The study divided patients into three groups of Group I (8 eyes in stage I), Group II (17eyes in stage II), and Group III (16 eyes in stage III). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…The stage of RAP has been proposed as a key factor in the effectiveness of treatment and prognosis. Early-stage lesions (stage I) seem to be associated with better visual and anatomical outcomes, whereas late-stage diseases (stage III) were reported to exhibit limited improvement with treatment by intravitreal injections of ranibizumab and bevacizumab [ 8 , 12 , 17 21 ]. In the current study, the baseline BCVA and CRT were similar among different stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stage of RAP has been proposed as a key factor in the effectiveness of treatment and prognosis. Early-stage lesions (stage I) seem to be associated with better visual and anatomical outcomes, whereas late-stage diseases (stage III) were reported to exhibit limited improvement with treatment by intravitreal injections of ranibizumab and bevacizumab [ 8 , 12 , 17 21 ]. In the current study, the baseline BCVA and CRT were similar among different stages.…”
Section: Discussionmentioning
confidence: 99%
“…During the 3-year study period, a significant decrease in BCVA was noted in eyes with stage II RAP at the second year, whereas eyes with stage I or stage III RAP could achieve stabilization in BCVA. Park and Roh [ 21 ] reported that three consecutive loading doses of intravitreally administered ranibizumab was an effective treatment for patients with stage I RAP within 1 year, resulting in a significantly lower recurrence rate than in patients in later stages. By contrast, our results indicated that an average of 5.3 ± 1.72 injections in the first year followed by a total of 10.4 ± 3.85 injections were required for patients with stage I RAP to maintain stabilized BCVA after 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Typ-3-MNV war nach 2 Jahren öfter inaktiv, obwohl die mediane Anzahl an Injektionen ähnlich denen in der Gruppe mit Typ-1- und Typ-2-MNV war [42]. Wenn die Läsion jedoch in einem früheren Stadium behandelt wurde, verringerte sich die Gesamtanzahl der nach 1 Jahr benötigten Injektionen [49]. Darüber hinaus waren die Ergebnisse bezüglich der Sehschärfe in Stadium 3 schlechter als in Stadium 2 und unerwünschte Ereignisse, die zu einer abrupten Visusverschlechterung führen können, entwickelten sich erst in Stadium 3 [50].…”
Section: Ergebnisseunclassified
“…in 29 % (IVRI) der Patienten. Auch Park und Mitarbeiter fanden insbesondere im Stadium 1 ein gutes Ansprechen auf Ranibizumab[81]. Tsaousis[82] und Matsumoto[83] publizierten ein entsprechendes Ansprechen unter Aflibercept-IVOM, Letzterer auch unter einem Treat-and-Extend-Regime (im Mittel 7,2 Injektionen im 1.…”
unclassified